Impact of Information and Communication Technologies on histology teaching: an integrative literature review (Research, Society and Development, 2022)
The aim was to identify the impact of the use of Information and Communication Technologies (ICTs) in the teaching of histology. This is an integrative literature review, qualitative and descriptive. We performed the search on October 2021, using the Virtual Health Library (VHL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Pubmed, and Science Direct as electronic databases. As a search strategy, the following descriptors in English and Portuguese were used: (“Information technology” AND “Histology”); (“Information technology” AND “Histology” AND “teaching”); (“Information and communication technology” AND “histology”). Original articles that answered the guiding question, in Spanish, English, and Portuguese, published between 2016 and 2021, were included. Four thousand one hundred and fifty-seven (4,157) articles were retrieved, and only seven were selected as eligible for the research. The ICTs present in the sample were Virtual Learning Environments (VLE), with Blackboard and Moodle platforms; Virtual Microscopy; and Digital Games, through the virtual game Kahoot!. The analysis of the data got shows that the impact of ICTs is positive and relevant for academic development, as they enable an interactive environment, capable of being accessed frequently and from different places, besides reinforcing the learning developed in a face-to-face environment. However, instability in the operating system, problems related to connectivity, or even the lack of access of some students to the internet network were perceived as challenges in using ICTs.